2017
DOI: 10.1039/c7nr06527b
|View full text |Cite
|
Sign up to set email alerts
|

Electro-oxidation of a cobalt based steel in LiOH: a non-noble metal based electro-catalyst suitable for durable water-splitting in an acidic milieu

Abstract: The use of proton exchange membrane (PEM) electrolyzers is the method of choice for the conversion of solar energy when frequently occurring changes of the current load are an issue. However, this technique requires electrolytes with low pH. All oxygen evolving electrodes working durably and actively in acids contain IrOx. Due to their scarcity and high acquisition costs, noble elements like Pt, Ru and Ir need to be replaced by earth abundant elements. We have evaluated a cobalt containing steel for use as an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 54 publications
(80 reference statements)
1
37
0
Order By: Relevance
“…substantially.T ot he besto fo ur knowledge, some of our group were the first to tailor steel intentionally into outstanding,e fficient, and stable OER electrocatalysts [56][57][58] on the basis of, inter alia, thin Ni, Fe oxide layers firmly attachedt ot he iron-based matrix. Benchmark OER properties were showna tp H13a nd pH 14, as the overpotential (h)a mounted to 212 mV at 12 mA cm À2 in 1 m KOH and to 269.2 mV at 10 mA cm À2 in 0.1 m KOH, respectively.V ery recently,h ydrothermal/electrochemicalo xidation of CrNi-based steel [59] as well as the surface oxidation of Ni42 [60] and X20CoCrWMo10-9//Co 3 O 4 steel [57,61] also provedt ob es uitable for the efficient preparation of acceptable OER catalysts that weres table and workedo ver a wide pH range. Besides surface oxidation, phosphorization and sulfurization have also been appliedt os teel, that is, Steel 316 (basically consisting of Ni, Cr,a nd Fe), to gain better overall OER characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…substantially.T ot he besto fo ur knowledge, some of our group were the first to tailor steel intentionally into outstanding,e fficient, and stable OER electrocatalysts [56][57][58] on the basis of, inter alia, thin Ni, Fe oxide layers firmly attachedt ot he iron-based matrix. Benchmark OER properties were showna tp H13a nd pH 14, as the overpotential (h)a mounted to 212 mV at 12 mA cm À2 in 1 m KOH and to 269.2 mV at 10 mA cm À2 in 0.1 m KOH, respectively.V ery recently,h ydrothermal/electrochemicalo xidation of CrNi-based steel [59] as well as the surface oxidation of Ni42 [60] and X20CoCrWMo10-9//Co 3 O 4 steel [57,61] also provedt ob es uitable for the efficient preparation of acceptable OER catalysts that weres table and workedo ver a wide pH range. Besides surface oxidation, phosphorization and sulfurization have also been appliedt os teel, that is, Steel 316 (basically consisting of Ni, Cr,a nd Fe), to gain better overall OER characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…5(e) at 852.6 eV and 851.2 eV corresponds to a metallic Ni peak and a satellite peak, respectively. [31][32][33][34] From these results, it may be concluded that Cr and Fe formed an oxide film on the surface of the SUS 304L, and that Ni in the metallic state was present close to the surface.…”
Section: Resultsmentioning
confidence: 86%
“…5(c) indicates metallic Cr, and the peak near 576.6 eV that of Cr oxide. [31][32][33][34] The peak at 706.9 eV in Fig. 5(d) is corresponding to metallic Fe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations